2022
DOI: 10.1024/1662-9647/a000266
|View full text |Cite
|
Sign up to set email alerts
|

The “Lost” Personality Disorders and Their Relationships to the Alternative Model of Personality Disorders Among Older Adults

Abstract: Abstract. Four personality disorders (PD) have become “lost” throughout the various editions of the DSM: Depressive, Passive-Aggressive, Sadistic, and Self-Defeating. The Alternative Model of Personality Disorders (AMPD) is a novel approach to PD classification, containing two diagnostic criteria: personality functioning and pathological personality traits. This study identifies the personality functioning and pathological personality trait features of the Lost PDs among older adults ( N = 202; Mage = 67.47 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…In addition, assessing relationships between intrapersonal functioning and diverse types of anxiety with interpersonal aspects of personality functioning (e.g., traditional PD symptoms) among older adults may be a logical future direction. Indeed, PDs in the older adult population are largely understudied, and further research should be directed toward a more complete understanding regarding anxiety and personality functioning in later life (Coolidge et al, 2000; Noel et al, 2021; Stone et al, 2021; Stone & Segal, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, assessing relationships between intrapersonal functioning and diverse types of anxiety with interpersonal aspects of personality functioning (e.g., traditional PD symptoms) among older adults may be a logical future direction. Indeed, PDs in the older adult population are largely understudied, and further research should be directed toward a more complete understanding regarding anxiety and personality functioning in later life (Coolidge et al, 2000; Noel et al, 2021; Stone et al, 2021; Stone & Segal, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Future studies would benefit from an increased focus on how sadism relates to the maladaptive personality traits formulated in DSM-5`s Alternative Model of Personality Disorders (AMPD) [16] and in the ICD-11 personality disorder chapter [25]. So far, there was only one study on the former that showed self-reported sadism traits to relate mostly to AMPD's callousness facet within the antagonism trait [73]. It could also be expected that sadism would further relate to the AMPD facets of hostility, manipulativeness, impulsivity, or deceitfulness-but the fact that this was not the case could potentially be ascribed to the study sample consisting of older adults [73].…”
Section: Suggestions For Future Studiesmentioning
confidence: 99%
“…So far, there was only one study on the former that showed self-reported sadism traits to relate mostly to AMPD's callousness facet within the antagonism trait [73]. It could also be expected that sadism would further relate to the AMPD facets of hostility, manipulativeness, impulsivity, or deceitfulness-but the fact that this was not the case could potentially be ascribed to the study sample consisting of older adults [73]. For the ICD-11, it could be expected that sadism would relate to dissociality and disinhibition traits.…”
Section: Suggestions For Future Studiesmentioning
confidence: 99%